Time to HIV viral rebound and frequency of post-treatment control after analytical interruption of antiretroviral therapy: an individual data-based meta-analysis of 24 prospective studies - Jesper D. Gunst; Jesal Gohil; Johanthan Z. Li; Ronald J. Bosch; Andrea White, Catherine Seamon; Tae-Wook Chun; Beatriz Mothe; Kathleen Gittens; Lauren Praiss; Marie-Angélique De Scheerder; Linos Vandekerckhove; Kevin Escandón; et al. (Nature Communications)
Abstract The only current strategy to test efficacy of novel interventions for sustained HIV control without antiretroviral therapy (ART) among people with HIV (PWH) is through an analytical treatment interruption (ATI). Inclusion of ‘placebo’ controls in ATIs poses ethical, logistical, and economic challenges. To understand viral dynamics and rates of post-treatment control (PTC) after ATI among PWH receiving either placebo or no intervention, we undertook an individual-participant data meta-analysis. In total, 24 eligible prospective studies with 382 individuals with ≥5 plasma HIV RNA viral loads (pVLs) within the first 84 days post-ATI were included. Early-ART was defined as ART initiation within 6 months of HIV acquisition; others were classified as late-ART or unknown. Median age was 42 years, 91% male, 75% white, 45% received early-ART. Median time to pVL >50, >400, and >10,000 copies/mL was 16 days (interquartile range [IQR]:13–25), 21 (IQR:15–28), and 32 (IQR:20–35), respectively. PTC defined as pVL <50 copies/mL at day 84 occurred in 4% (n = 14) of participants (6% early-ART and 1% late-ART). Sustained PTC of pVL <50 copies/ml after 84 days is rare in PWH, especially in those starting ART late. Our findings inform future interventional HIV cure/remission trials on study size and design.